Detection and profiling of antimicrobial resistant Escherichia coli and Salmonella spp. in tilapia and shrimp sold at Dhaka’s wet markets, Bangladesh - Rheman, Shafiq; Hossain, Sabrina (WorldFish, 2024)
WorldFish, as a non-profit research organization, is working with different government and non-government organizations in Bangladesh on different aspects of fisheries and aquaculture. WorldFish signed a memorandum of understanding (MOU) to collaborate in the area of aquatic animal health management. In this context, WorldFish delivered a talk to Masters students organized by Fisheries and Marine Resources Technology Discipline (FMRT), Khulna University, Bangladesh. The main objective of this talk was to discuss the findings of a recent study related to antimicrobialresistant Escherichia coli and Salmonella spp. The talk entiled as “Detection and profiling of antimicrobialresistant Escherichia coli and Salmonella spp. in tilapia and shrimp sold at Dhaka’s wet markets, Bangladesh” was divided into two sessions.